Recommendations of the Italian society for infectious and tropical diseases (SIMIT) for adult vaccinations - Massimo Andreoni; Laura Sticchi; Silvia Nozza; Loredana Sarmati; Andrea Gori; Marcello Tavio; Society for Infectious and Tropical Diseases (SIMIT) (Taylor & Francis Group, 2021)
Vaccination prevents 2-3 million deaths worldwide every year. Nevertheless, vaccine-preventable diseases (VPDs) still cause a considerable number of deaths especially in subjects belonging to "risk groups." These are represented by older adults, immunocompromised individuals and all subjects with underlying chronic medical conditions (cardiovascular, pulmonary, renal and liver chronic diseases, diabetes, immunodeficiency disorders). They have a weaker immune system and, if infected, are more likely to develop severe complications of their condition or of the preventable-infectious disease. This document summarizes the recommendations for vaccination of the main Global Institutional Organizations and analyses the risks of comorbidities associated with infectious disease and the benefits of vaccination for each specific group. The document provides a clear, practical and authoritative guide to adult vaccination.